In vitro antimicrobial activity of acroseal, polifl and epiphany against Enterococcus faecalis - Pinheiro, Cláudia Ramos [UNESP]; Guinesi, Adriana Simionatto [UNESP]; Pizzolitto, Antônio Carlos [UNESP]; Bonetti-Filho, Idomeo [UNESP] (FapUNIFESP (SciELO), 2009)
Using the agar diffusion method, this study evaluated the in vitro antimicrobial activity of the commercial endodontic sealers Acroseal and Epiphany, a castor-oil based experimental sealer, Polifl, and a primer agent (Epiphany self-etching primer), against Enterococcus faecalis. Zinc oxide and eugenol cement (ZOE) served as control. Five wells per dish were made at equidistant points and immediately flled with the test and control materials. After incubation of the dishes at 37°C for 24 h and 48 h, the diameter of the zones of microbial growth inhibition produced around the wells was measured (in mm) with a millimeter rule. After 48 h, the diameters of the zones of microbial growth inhibition were the same as those observed at 24 h, only the substances continued to diffuse. Epiphany and Polifl did not show antibacterial activity (no formation of zones of microbial growth inhibition). The primer produced the largest zones of inhibition (17.62 mm) followed by Acroseal (7.25 mm) and ZOE (7.12 mm). E. faecalis was resistant to Epiphany and Polifl, while the primer and Acroseal sealer were effective against this microorganism under the tested conditions.
Keywords: Antibacterial activity; Endodontic sealers; In vitro study; Acroseal; epiphany sealer; polifil; root canal filling material; disk diffusion; drug effect; Enterococcus faecalis; Disk Diffusion Antimicrobial Tests; Root Canal Filling Materials